Human acellular dermal matrix allograft: A randomized, controlled human trial for the long-term evaluation of patients with extensive burns. Issue 4 (June 2015) - Li, Xueyong; Meng, Xianghai; Wang, Xiaolin; Li, Yuejun; Li, Wangzhou; Lv, Xiaoxing; Xu, Xiaoli; Lei, Zhanjun; Li, Jinqing
Highlights We evaluated the long-term outcomes of the grafting with ADM for the coverage of wounds. The proportion of collagen III/I was lower in the ADM group. The basement membrane was prominent and continuous in the ADM group. The composite graft of ADM was suitable for repairing functional areas.